2013
DOI: 10.1177/1933719112472737
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Culture of Ovarian Cortical Strips From Capuchin Monkeys (Sapajus apella): A Morphological, Viability, and Molecular Study of Preantral Follicular Development In Vitro

Abstract: The aim of this study was to evaluate whether an in vitro culture (IVC) medium containing either or not b-mercaptoethanol (BME), bone morphogenetic protein 4 (BMP4), or pregnant mare serum gonadotrophin (PMSG) could be able to promote the development of capuchin monkeys' preantral follicles enclosed in ovarian cortical strips. Follicular viability after IVC was similar to control (89.32%). Primordial follicle recruitment to primary stage was not reached with IVC, but the rate of secondary follicle formation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…because it indicates that the captive group or individuals are robust capuchins, providing more information than the blanket use of Cebus spp., a term that could be interpreted by researchers as specifically signifying gracile capuchins. There is currently a divide in the literature in which most field researchers working with robust capuchins publish their work as Sapajus in concert with the species and sometimes subspecies for the given location [e.g., Falotico & Ottoni, ; Fragaszy et al, ; Scarry, ] while captive researchers publish work with any captive robust capuchin monkey populations or medical research subjects variously as C. apella [Addessi et al, ; Phillips & Thompson, ; Wheeler et al, ], S. apella [Brito et al, ; Morton et al, ; Rimpley & Buchanan‐Smith, ], Sapajus spp. [Goulart et al, ], or S .…”
Section: Discussionmentioning
confidence: 99%
“…because it indicates that the captive group or individuals are robust capuchins, providing more information than the blanket use of Cebus spp., a term that could be interpreted by researchers as specifically signifying gracile capuchins. There is currently a divide in the literature in which most field researchers working with robust capuchins publish their work as Sapajus in concert with the species and sometimes subspecies for the given location [e.g., Falotico & Ottoni, ; Fragaszy et al, ; Scarry, ] while captive researchers publish work with any captive robust capuchin monkey populations or medical research subjects variously as C. apella [Addessi et al, ; Phillips & Thompson, ; Wheeler et al, ], S. apella [Brito et al, ; Morton et al, ; Rimpley & Buchanan‐Smith, ], Sapajus spp. [Goulart et al, ], or S .…”
Section: Discussionmentioning
confidence: 99%
“…The competence of oocytes retrieved from antral follicles in capuchin monkeys was achieved after 36 hours of IVM, the highest maturation rate occurring in oocytes collected from dominant follicles [71]. It has also demonstrated that the IVC of ovarian cortical strips in TCM199 supplemented of β-mercaptoethanol (BME), bone morphogenetic protein 4 (BMP4), or pregnant mare serum gonadotrophin (PMSG) promoted a follicular viability similar to that of controls (89.3%) for this species, while it also increases the rate of secondary follicle formation (44.9%) [70].…”
Section: In Vitro Culture and Maturation Of Oocytesmentioning
confidence: 94%
“…The recovery of oocytes by mechanical preantral follicle (PF) isolation in ovariectomy specimens [69], the collection of ovarian biopsies by exploratory laparoscopy [70], and the puncture of antral follicles by laparotomy [71] have been described studies in capuchin monkeys (Sapajus apella). In marmoset monkeys, oocyte recovery was achieved through follicle aspiration after laparotomy [72], laparoscopy [65], or uni-or bilateral ovariectomy [73].…”
Section: Recovery Of Female Gametesmentioning
confidence: 99%
“…The possibility of in vitro culture (IVC) and maturation (IVM) of such oocytes would provide datum about the folliculogenesis and offer opportunities for their use in others reproductive techniques (Comizzoli, Songsasen, & Wildt, 2010;Green & Shikanov, 2016). In this context, the IVC of PFs enclosed in ovarian tissue represents a practical alternative for these studies, once it avoids the risks of follicular damages and losses provoked by the isolation (Brito et al, 2013). However, the required conditions for the complete in vitro development of PFs are not established, especially for wild species, once data regarding follicular | 881 and oocyte growth are scarce (Green & Shikanov, 2016;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%